Consumption and Debt Response to Unanticipated Income Shocks: Evidence from a Natural Experiment in Singapore - Agarwal, Sumit; Qian, Wenlan (American Economic Review, 2014)
This paper uses a unique panel dataset of consumer financial transactions to study how consumers respond to an exogenous unanticipated income shock. Consumption rose significantly after the fiscal policy announcement: during the ten subsequent months, for each $1 received, consumers on average spent $0.80. We find a strong announcement effect—19 percent of the response occurs during the first two-month announcement period via credit cards. Subsequently, consumers switched to debit cards after disbursement before finally increasing spending on credit cards in the later months. Consumers with low liquid assets or with low credit card limit experienced stronger consumption responses. (JEL D12, D14, E21)